2013
DOI: 10.4236/ojog.2013.31a039
|View full text |Cite
|
Sign up to set email alerts
|

Double balloon device compared to oxytocin for induction of labour after previous caesarean section

Abstract: Objective: To assess cervical changes, duration of oxytocin infusion, mode of delivery and complications after cervical ripening using a double balloon device in women with a previous caesarean section. Methods: Longitudinal study including 80 women with a previous caesarean section, no previous vaginal delivery and an unfavourable cervix (Bishop score < 4). Two groups were established: a double balloon device was used with 32 women (exposed) and not with the others (non-exposed) (48). Statistical analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Table 4 summarises the findings from some of the studies [8][9][10][11] including the current study. Most of the studies showed significant improvement in Bishop score after using the device and a favourable cervix was achieved in 75% to 85% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 summarises the findings from some of the studies [8][9][10][11] including the current study. Most of the studies showed significant improvement in Bishop score after using the device and a favourable cervix was achieved in 75% to 85% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…A second potential reason for better outcomes in our study would lie in the differences in inclusion criteria. Some studies had excluded women with previous vaginal delivery, 10 a factor known to be associated with successful VBAC. A third reason could have been differences in ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies [16][17][18][19][20][21][22][23] have specifically reported on the use of DBC for cervical ripening among women with PCD and an unfavorable cervix. Table 4 compares the findings of these investigations with those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In women with an unscarred uterus, mechanical induction demonstrates a lower incidence of uterine hyperstimulation and similar CSR compared with locally applied prostaglandins 34 38 41–47. Similarly, women with a previous CS induced with FCB showed no differences in uterine scar rupture rates when compared with spontaneous labour or IOL with amniotomy or oxytocin 48–53…”
Section: Introductionmentioning
confidence: 95%